Development Of An Automated Compilation Test System For Embedded System Testing - Ooi , Jun Hwan (2016)

(untitled)
In the embedded system testing which involved the integration testing between both software and hardware, it becomes increasingly difficult to evaluate the functionality of each functional modules in a short time due to the increasing number of testing required. This research proposed an automated compilation test system through a design structure to improve the quality of testing and optimize the testing time using automation. In other words, the testing coverage can be maximized with minimum manual work and testing time required. This test system has been used to automate the test code compilation and execution for different hardware module testing. The result analysis from the implementation of proposed test system proved that there is a significant testing time saving for around 56.42% besides ensuring the performance and quality of the result. In summary, this research has proposed an automated compilation test system which contributes in time saving and quality assurance for test code compilation and execution process.